2013
DOI: 10.1128/genomea.00135-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of a Francisella tularensis subsp. holarctica Strain from Germany Causing Lethal Infection in Common Marmosets

Abstract: Here, we describe the genome sequence of the Francisella tularensis subsp. holarctica strain F92, belonging to the Franco-Iberian subgroup. This strain represents the first-time isolate of this subgroup in Germany and was obtained from naturally infected marmosets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Several genome sequences of F. tularensis subsp. holarctica are published but only a limited number of genomes has been fully assembled and annotated ( Larsson et al, 2005 , 2009 ; Beckstrom-Sternberg et al, 2007 ; Chaudhuri et al, 2007 ; Rohmer et al, 2007 ; Barabote et al, 2009 ; Champion, 2011 ; Modise et al, 2012 ; Sjodin et al, 2012 ; Svensson et al, 2012 ; Antwerpen et al, 2013 , 2015 ; Atkins et al, 2015 ; Busch et al, 2017 ). The here described assembly is a high quality full genome sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Several genome sequences of F. tularensis subsp. holarctica are published but only a limited number of genomes has been fully assembled and annotated ( Larsson et al, 2005 , 2009 ; Beckstrom-Sternberg et al, 2007 ; Chaudhuri et al, 2007 ; Rohmer et al, 2007 ; Barabote et al, 2009 ; Champion, 2011 ; Modise et al, 2012 ; Sjodin et al, 2012 ; Svensson et al, 2012 ; Antwerpen et al, 2013 , 2015 ; Atkins et al, 2015 ; Busch et al, 2017 ). The here described assembly is a high quality full genome sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequencing has been performed on several F. tularensis and F. novicida strains, with a limited number of genomes fully assembled and annotated (Larsson et al, 2005 ; Beckstrom-Sternberg et al, 2007 ; Chaudhuri et al, 2007 ; Rohmer et al, 2007 ; Barabote et al, 2009 ; Champion et al, 2009 ; Larsson et al, 2009 ; Modise et al, 2012 ; Sjödin et al, 2012 ; Svensson et al, 2012 ; Antwerpen et al, 2013 ). Consistent with the high degree of genetic similarity previously determined via DNA-DNA re-association (Hollis et al, 1989 ), the average nucleotide identity observed across 1.1 MB of genomic sequence from 3 F. novicida strains and 13 F. tularensis strains (8 subsp.…”
Section: Genomicsmentioning
confidence: 99%
“…Consistent with the previous observation that Lon predominantly cleaves substrates at the hydrophobic amino acids 29 , 37 , 8 of the 15 Lon substrates were composed of more than 40% nonpolar amino acids (FTL196, FTL578, FTL964, FTL1003, FTL1167, FTL1216, FTL1228, and FTL1935) (Table S4 ). However, this trial did not reveal any obvious biochemical characteristics shared by all of the Lon substrates although they represent an extreme small fraction of the 1800 cellular proteins encoded by the Francisella genomes 46 48 .…”
Section: Resultsmentioning
confidence: 72%